Gerontechnology: rapid review and global trends - De la Torre, F.; Morales, D.; Quiroz, C. P. (Revista Mexicana de Ingenieria Biomedica, 2015)
Current demographic and epidemiological transitions being experienced by several regions in the world, including Mexico, are challenging the sustainability of health systems, leading to the development of new approaches to care for the elderly population. The core strategy is focused on healthy aging where increased life expectancy is free of disability. Gerontechnology intended to help reduce the problems of seniors that involve transitions of aging by supporting the implementation of the core strategy. Conducting rapid review in gerontechnology shows that the Netherlands and United States top the list of countries promoting research and gerontechnology developments worldwide, with 14 and 10 publications respectively. Mexico contributes to the generation of knowledge in the field with one publication. Worldwide the trend is the generation of multidisciplinary groups with science professionals on Sociology, Demography (Gerontology) in conjunction with professionals in the areas of Communication and Information Technology (Technology); having as main objective the support and organization in care of the elderly in the domains of Housing and Activities of Daily Living.